2016
DOI: 10.1002/ijc.30168
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Fusobacterium nucleatum may play a role in the carcinogenesis of proximal colon cancer through the serrated neoplasia pathway

Abstract: The prevalence of invasive Fusobacterium nucleatum (Fn) within the serrated neoplasia pathway of the proximal colon has seldom been investigated. We examined the invasive Fn and bacterial biofilms in 35 proximal hyperplastic polyps (HPs), 33 sessile serrated adenomas (SSAs), 48 proximal colorectal cancers (CRCs) and 10 matched metastatic lymph nodes using 16S rRNA fluorescence in situ hybridization (FISH). Samples of normal mucosa, traditional adenomas (TAs), distal HPs, distal CRCs and matched lymph nodes wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
96
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(104 citation statements)
references
References 44 publications
(126 reference statements)
6
96
1
1
Order By: Relevance
“…Tomkovich et al recently reported that human colon mucosal biofilms were carcinogenic in murine CRC-models, whether the biofilm associated microbiota were from CRC-patients or healthy individuals [104]. Yu et al detected biofilms associated with CRC, adenomas, and polyps by SEM, FISH, and fluorescence microscopy and found that the prevalence of F. nucleatum was significantly higher in biofilms from CRC than the other sample groups [105]. Although a connection between the composition of the colorectal microbiota and CRC is becoming increasingly evident, more research is needed to determine the exact role of the microbial community of the biofilm and its constituting species in carcinogenesis.…”
Section: Inflammatory Bowel Disease and Colorectal Cancermentioning
confidence: 99%
“…Tomkovich et al recently reported that human colon mucosal biofilms were carcinogenic in murine CRC-models, whether the biofilm associated microbiota were from CRC-patients or healthy individuals [104]. Yu et al detected biofilms associated with CRC, adenomas, and polyps by SEM, FISH, and fluorescence microscopy and found that the prevalence of F. nucleatum was significantly higher in biofilms from CRC than the other sample groups [105]. Although a connection between the composition of the colorectal microbiota and CRC is becoming increasingly evident, more research is needed to determine the exact role of the microbial community of the biofilm and its constituting species in carcinogenesis.…”
Section: Inflammatory Bowel Disease and Colorectal Cancermentioning
confidence: 99%
“…The unique FadA adhesin of F. nucleatum can bins to E-cadherin, which activates β-catenin signaling, inducing oncogenic responses in CRC cells. 93 This is accompanied by increasing expression of transcription factors, oncogenes, Wnt, and inflammatory genes, together with growth promotion of CRC cells. 94 By releasing RNA into the host cell and activating NF-κB, F. nucleatum induced inflammation.…”
Section: Fusobacterium Nucleatummentioning
confidence: 99%
“…Numerous recent studies have reported that the anaerobic Gram-negative oral commensal bacterium, Fusobacterium nucleatum, plays a significant role in colorectal carcinogenesis [8][9][10][11][12][13][14]. F. nucleatum has been detected iñ 10-90% CRC tissues, with higher prevalence in the proximal than distal colon [15][16][17]. It is often associated with advanced disease, chemo-resistance, metastasis, and poor prognosis [14,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%